An Attempt of Geopolymer Synthesis from Construction Waste - Jha, Vinay Kumar; Tuladhar, Anupama (Journal of Nepal Chemical Society, 2013)
Recently, the demolition of old houses and the construction of new buildings in Kathmandu valley are in the peak which in turn generates a huge amount of construction waste. This construction waste is rich source of alumino-silicate and thus used as raw material for the synthesis of geopolymer in this study. Geopolymers have been synthesized from construction waste using NaOH and Na2SiO3 as activators. Some parameters like alkali concentration, ratio of Na2SiO3 to construction waste and curing time have been varied in order to improve the quality of geopolymeric product. The results obtained revealed the maximum compressive strength of 7.3 MPa at the ratio of sodium silicate to construction waste of 0.5 (w/w) on 15 days curing time at 40ºC temperature. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8038 Journal of Nepal Chemical Society Vol.28, 2011 Page 29-33 Uploaded date: March 6, 2013